Sales forecast for aromatic dwarf coconut: a case study of Hutan Melintang in Perak / Nurhuda Ismail ... [et al.] - Ismail, Nurhuda; Raseli, Siti Sarah; Mahat, Norpah; Abdul Razak, Siti Nor Suhada (Universiti Teknologi MARA, Perak, 2022)
Aromatic Dwarf Coconut known as Compact Dwarf coconut is a wellknown plant in Malaysia, especially in Hutan Melintang, Perak. Forecasting the sales of Aromatic Dwarf Coconut should be apply innovatively to increase the production of the Aromatic Dwarf Coconut compared with the traditional accounting technique. Revenue’s Data of Aromatic Dwarf Coconut generated from Jabatan Pertanian Teluk Bharu, Hutan Melintang, Perak from the year 2015 to the year 2019 shows that the sales of Aromatic Dwarf Coconut increased every month and every year. The objectives of this research are; 1) to forecast the sales of Aromatic Dwarf Coconut using Artificial Neural Network (ANN) and Linear Algebra and 2) to compare these two methods which are gives the minimize error interpreted by Mean Square Error (MSE). This research used secondary data of State Departments of Agriculture, Jabatan Pertanian Teluk Bharu tested with Artificial Neural Network (ANN) and Linear Algebra model to forecast the sales of Aromatic Dwarf Coconut for 2020. The findings show that the result from the forecast sales for the 1st quarter of Linear Algebra method is higher than ANN. Based on the MSE result, the ANN method shows minimized error which is more accurate rather than the Linear Algebra method. Forecasting methods such as ANN and Linear Algebra were able to assist the company to predict the sales of Aromatic Dwarf Coconut in the future.